Evaluation of thermal pretreatment and digestion temperature rise in a biogas fueled combined cooling, heat, and power system using exergo-economic analysis. (1st May 2018) - Mirmasoumi, Siamak; Khoshbakhti Saray, Rahim; Ebrahimi, Sirous
Highlights: Thermal pretreatment and thermophilic digestion of sewage sludge were evaluated. Thermophilic digestion significantly increased the biomethane productivity. Energy recovery balance of the applied techniques were positive. Thermophilic digestion drastically decreased the levelized cost of energy. Abstract: In a municipal wastewater treatment plant, the anaerobic digesters are able to support the whole or a portion of the required fuel to offset the energy demand. Also, by implementing some techniques on municipal sewage sludge, leading to biomethane productivity enhancement, it is possible to generate surplus power. In this work, using batch biomethane potential assays, thermal pretreatment at 70 °C & 90 °C for the durations of 0.5 h, 1 h, 2 h, 3 h, and 4 h, and digestion temperature rise from the mesophilic to the thermophilic conditions have been studied to boost the biomethane productivity of the sewage sludge. Also a combined cooling, heat, and power generating plant was suggested to evaluate the techniques thermo-economically. It was shown that, compared to the non-treated mesophilic digestion of the sewage sludge, thermal pretreatment at 70 °C and 90 °C for 0.5 h, and thermophilic digestion were able to raise the biomethane productivity by 13.63%, 59.82%, and 160.8%, respectively. In this regard, the thermodynamic and the thermo- economic model of the plant was developed. The energy analysis of the system revealed that not only the studied methods, but also the mesophilic digestion of the non-treated sewage sludge result in a positive energy recovery balance in the plant. The exergo-economic analysis indicated that the major origin of cost in the system is the anaerobic digester. Implementing thermal pretreatment at 90 °C for 30 min and digestion temperature rise led to decrease in the required volume of the digester, and subsequently, in the total system cost rate. Additionally, all the applied techniques provided more fuel compared to the non-treated mesophilic case, and consequently they could reduce the levelized cost of energy in the plant. Among the studied techniques, the most effective one was digestion temperature rise which decreased the total cost rate and the levelized cost of energy by 30.31% and 41.29%, respectively.